Genetic heterogeneity in Gaucher disease. Issue 4 (August 1986) - Zlotogora, J; Zaizov, R; Klibansky, C; Matoth, Y; Bach, G; Cohen, T
Abstract : Considerable clinical variability occurs in adult Gaucher disease type I and three main subtypes may be delineated: a very mild form, a severe form, and a moderate form which itself presents various clinical manifestations. A study based on 25 families from our clinic and a review of published reports showed that when both parents were heterozygous and more than one child was affected with Gaucher disease type I, there was always intrafamilial similarity concerning the three subtypes. In families where one parent and at least one child were affected, variability in the clinical subtype of Gaucher disease type I might occur among the affected members of the family. We propose that the three different clinical subtypes of this disease reflect the genetic heterogeneity of two alleles, G1a and G1b and the three corresponding genotypes represent the three different subtypes of the disease.